Neoadjuvant Chemo-Radiotherapy for Patients with Borderline Resectable Pancreatic Cancer: A Meta-Analytical Evaluation of Prospective Studies - Festa, Virginia; Andriulli, Angelo; Valvano, Maria Rosaria; Uomo, Generoso; Perri, Francesco; Andriulli, Nicola; Corrao, Salvatore; Koch, Maurizio (JOP. Journal of the Pancreas, 2013)
Context For patients with borderline resectable pancreatic cancer, the benefit of neoadjuvant therapy remains to be defined. Objective We did a systematic search of the literature on this topic. Methods Prospective studies where chemotherapy with or without radiotherapy was given before surgery to patients with borderline resectable cancer, were analyzed by a meta-analytical approach. Main outcome measures Primary outcome was surgical exploration and resection rates; tumor response, therapy-induced toxicity, and survival were secondary outcomes. Data were expressed as weighted pooled proportions with 95% confidence intervals (95% CI). Results Ten studies with 182 participants were included. Following treatment, 69% of patients (95% CI: 56-80%) were brought to surgery and 80% (95% CI: 66-90%) of surgically-explored patients were resected. Eighty-three percent (95% CI: 74-90%) of resected specimens were deemed R0 resections. The weighted fractions of resected patients alive at 1 and 2 years were 61% (95% CI: 48-100%) and 44% (95% CI: 32-59%), respectively. At restaging following neoadjuvant therapy, weighted frequencies for complete/partial response were 16% (95% CI: 9-28%), 69% (95% CI: 60-76%) for stable disease, and 19% (95% CI: 13-25%) for progressive cancer. Treatment-related grade 3-4 toxicity was 32% (95% CI: 21-45%). Conclusion This meta-analysis shows that downstaging of the lesion following neoadjuvant therapies is uncommon for patients with borderline resectable pancreatic cancer. A clear benefit of this regimen could be to spare surgery to patients with progressive disease during the frame-time chemo-radiotherapy is being delivered. Image: PRISMA 2009 flow diagram.